Design and Implementation of Context Aware Applications with Wireless Sensor Network Support in Urban Train Transportation Environments - A. S. Rathore (Mathematical Statistician and Engineering Applications, 2023)
Farmers may optimize irrigation schedules, control crop health, and boost production while conserving water and resources by installing sensor nodes in fields. This allows farmers to maximize profits while minimizing waste. In addition, wireless sensor networks make it easier to monitor weather conditions, pest infestations, and crop diseases. This gives farmers the ability to take early decisions to safeguard their crops and have the greatest possible impact on their output. In addition, wireless sensor networks (WSNs) are utilized extensively in industrial automation and monitoring applications. These applications make it possible to monitor infrastructure, machinery, and equipment in real time. The deployment of sensor nodes in factories, warehouses, and other industrial facilities enables wireless sensor networks (WSNs) to improve condition monitoring, predictive maintenance, and asset tracking. This results in the prevention of equipment failures, the reduction of downtime, and the optimization of production processes. Further, wireless sensor networks make it possible to remotely monitor vital characteristics like temperature, pressure, and vibration, which helps to ensure that operations are carried out both efficiently and safely. Wireless sensor networks (WSNs) are utilized in the healthcare industry for the purpose of remote patient monitoring. This allows medical practitioners to accurately monitor vital signs, identify irregularities, and give prompt medical intervention. Sensor nodes that are implanted in patients or included in wearable devices capture physiological data such as heart rate, blood pressure, and glucose levels. This data is then wirelessly sent to healthcare practitioners for examination. Additional applications that are supported by WSNs include ambient assisted living apps. These applications monitor the activities of persons who are old or disabled and offer aid and support in the event of an emergency. The implementation of wireless sensor networks (WSNs) in smart cities is another key use of these networks, since they contribute to the administration and optimization of metropolitan infrastructure in a variety of ways. In order to improve traffic management, reduce emissions, and increase public safety, wireless sensor networks (WSNs) make it possible to create intelligent transportation systems that monitor traffic flow, vehicle congestion, and air quality.